OPTIMALISASI PUPUK ORGANIK LOKAL LUMAJANG: ANALISIS STRATEGIS UNTUK MENINGKATKAN KEBERLANJUTAN DAN PREFERENSI PETANI - Silalahi, Amin; Karnadi, Karnadi; Watunglawar, Balthasar (Growth, 2025)
Organic fertilizer is a sustainable solution to improve soil fertility and food security in Lumajang, East Java. P4S Asri Farm Kedungrejo faces competition from fertilizer producers in Banyuwangi, such as Gondruwo Fertilizer, which has achieved an 80% customer satisfaction rate. Quantitative data shows that 65% of farmers have shifted to Banyuwangi fertilizers, while only 35% prefer local products. Crop yields increased by 15% after using Banyuwangi fertilizer. This study investigates the impact of external fertilizer adoption on local business sustainability and factors influencing farmer preferences, including product trust and quality. Using SWOT analysis and farmer surveys, recommended strategies include product diversification, branding enhancement, and farmer education on local fertilizer benefits. Strategic collaborations with Banyuwangi producers can also improve local product competitiveness. Results indicate that despite intense competition, innovation and targeted marketing can ensure business resilience and growth. The conclusion emphasizes the importance of product innovation, quality improvement, and community-based marketing to maintain local market share and support sustainable enterprise development.